Exploring The Representation of Friendly Islam in Muslim-Non-Muslim Relations in Banyuwangi - Bahar, Moh Syaeful; Ali, Ahmad Khubby; Harnadi, Dodik (Millati: Journal of Islamic Studies and Humanities, 2024)
One of the causes of harmonious relations between religious communities is often associated with the role of Islamic practices among Muslims in Indonesia. As adhered to by Indonesian Muslims, Islam is believed to represent a friendly understanding of Islam. Several studies on Islam in Indonesia consistently emphasize this Islamic practice with various related terminology. However, how Muslims who are directly involved in harmonious relations with non-Muslims view friendly Islamic practices has not been widely explored. This research aims to fill this empirical gap by investigating how Nahdliyyin Muslims in Bulurejo, Purwoharjo Banyuwangi, define their Islamic practices. In this region, Muslims live side by side in harmony with Hindu and Christian communities. In addition, this research also reveals how Muslims take action, using Giddens’ perspective, in presenting this friendly form of Islam. By using qualitative-interpretive methods, this research found that Muslims in Banyuwangi define friendly Islam through various aspects of their practices, such as pro-existence, respect for diversity, and more. Meanwhile, as agents, Muslims in Banyuwangi consciously present friendly Islam based on arguments and motivations conveyed discursively.